Sacral Ewing sarcoma with rib, lung, and multifocal skull metastases: A rare case report and review of treatments - Ye, Chen; Wei, Wei; Tang, Xuebin; Li, Feng; Xin, Baoquan; Chen, Qianqian; Wei, Haifeng; He, Shaohui; Xiao, Jianru (Frontiers in Oncology, 2022)
Ewing sarcoma (ES) rarely derives from the sacrum or mobile spine. The discovery of primary ES with multimetastatic involvements is exceedingly less frequent in clinical practice. A 23-year-old man with initial primary sacral ES developed metastases of rib, lung, and multifocal skull after receiving surgical intervention and series of adjuvant therapies. We provide this very rare case consisting of its clinical features, imaging findings, treatments, and outcomes. Therapeutic modalities of ES are also reviewed in previous published articles. The prognosis of metastatic ES remains dismal; effective therapeutic modalities for ES require multidisciplinary collaboration, with more high-quality clinical trials to promote the optimal protocols.